Comparison of empirical propagation path loss models for mobile communications in the suburban area of Kuala Lumpur - Chebil, Jalel; Lwas, A.K.; Islam, Md. Rafiqul; Zyoud, A. H. (2011)
The empirical propagation path loss models have important influence in mobile communication systems design. They become important tools in both research and industrial communities owing to their speed of implementation and their limited dependence on detailed knowledge of the terrain. The mobile services are increasing rapidly and hence the mobile stations are required to design with best quality of service. Path loss models are considered frequently to estimate power budgets and cell coverages. Four empirical models namely, the Lee model, the Stanford University Interim (SUI) model, the COST-231 Hata model and Egli model have been investigated in this work. The measurements were carried out at University Putra Malaysia (UPM) campus and Gombak area. The measured data is used to validate the applicability of the four models mentioned previously in suburban environments. The results show that Egli model, COST-231 Hata model and SUI model over-predict the path loss in all coverage areas. The Lee model shows the best performance to the measured path loss.